KEKUATAN EKSEKUTORIAL PUTUSAN PTUN (ANALISIS PELAKSANAAN PUTUSAN PTUN PADA KASUS PERIZINAN PERTAMBANGAN PT. TMS) - Asep Misbach Alfaridzi; Muhammad Hilmi Naufal Aflah; Najmi Rabbani (Universitas Stikubank, 2023)
The PTUN’s decision are often not obeyed and implemented by state administrative officer. When the decision of PTUN doesn’t have executorial effect, judicial control which is owned by the PTUN as a form of implementing good governance in Indonesian state administration will be unclear. One of the problem occurs in the realm of mining business license. Government as the publisher of mining business license is often reluctant to comply with PTUN decisions to revoke decree on business license that violate the law. The purpose of this study is to determine the compliance level of the Minister of Energy and Mineral Resources and PT. Tambang Mas Sangihe (PT. TMS) to PTUN decision. The method of this study uses a normative juridical research model. While the data collection technique of this study uses library method. The results of this study shows that the disputed object “Decree of Minister of Energy and Mineral Resources Number: 163.K/MB.04/DJB/2021” is considered that have violated the law and general principle of good governance. As consequence, in PTTUN Jakarta's decision, the Minister was ordered to revoke the decree of mining permit for PT. TMS. However, the decision was not implemented by the Minister and PT. TMS. Keywords : Administrative court, Administrative court decision, executive power.